Statistical Analysis of Sequence Characteristics of Single Transmembrane Cluster of Differentiation Proteins: A Study of Functional Relevance - Patterson, Ashlie Kiel (My University, 2012)
Cluster of Differentiation (CD) proteins are human white blood cell markers involved in immune reactions. They are used as targets for immunological studies, diagnostic techniques of disease states as well as utilized in therapeutic applications for cancers and other maladies of the body. Analysis of sequence characteristics of CD proteins has enabled the identification of functional trends that may be useful in understanding their roles within the immune system. Through statistical analysis, Principal components analysis (PCA) and K-means clustering, 36 Type II CD proteins were analyzed by one hundred twenty-four biochemical and biophysical properties derived from amino acid sequences alone. The analysis revealed these 36 CD proteins can effectively be grouped into two distinct known functional groups. In addition, possible unknown functional properties of CD71 have been identified specifically. This research shows the potential for a quantitative approach in proteomics to unlock predictive capabilities. It is believed that upon the basis of this analytical technique, functional properties may be predicted of currently undiscovered CD proteins as well as known, poorly characterized CD proteins.
Keywords: Transmembrane Cluster; Protiens; Biology; proteomics; Cluster of Differentiation; diagnostic techniques; immunological; white blood cell